Epidemiology & Infection (Cambridge)
Epidemiology and Infection publishes original reports and reviews on all aspects of infection in humans and animals. Particular emphasis is given to the epidemiology, prevention and control of infectious diseases. The field covered is broad and includes the zoonoses, tropical infections, food hygiene, vaccine studies, statistics and the clinical, social and public-health aspects of infectious disease.
Keywords: Epidemiology